Converting school buildings into senior care facilities in China: urban and rural approaches - Xiaolian Yu; Satoshi Ishii (Journal of Asian Architecture and Building Engineering)
This paper explored the process and situation of converting abandoned schools into senior care facilities in China and compares the differences between urban and rural approaches to and uses of conversion. It took examples of urban and rural conversions to make a comparative analysis of building plans and functions, surrounding environmental resources, differences in facility usage, and environmental evaluations, clarifying the difference in approaches to urban and rural conversion and providing a reference for future conversion practices. As this paper illustrated, the number of existing rural conversions is three times higher than that of urban areas, and most cases are in China’s central and eastern regions. Most abandoned school buildings in rural areas are self-built, with brick and concrete structures. There is also an overall lack of funding, and 66% of the rural cases have an investment amount of 5 million RMB or less. The above sums up the characteristics of conversion cases all over China. In addition, this paper also summarized the current status and design emphasis of the rural and urban conversions.